Mushkilāt Ta‘līmi al-Lughah al-‘Arabiyyah fī Thailand wa al-Ḥulūl ‘Alaiha - Masrupi Masrupi; Nurul Murtadho; Ibnu Samsul Huda (Alsina : Journal of Arabic Studies, 2020)
The present research aims to describe linguistic and non-linguistic problems in Arabic learning process at “Songserm Wittaya Mulnithi Kuttao”, Thailand and to offer alternative solutions for both. This research uses descriptive qualitative research methods. The result of this research are linguistic and non-linguistic problems; the linguistic problems are the difficulty in pronouncing some Arabic letters, the presence of tashrif in Arabic, and the differences in sentence arrangement and the non-linguistic problems are the learning method I used did not have any variation, the learning media I used did not have any variation, and the students are not motivated to learn Arabic. The alternative solutions to the linguistic problem are the repeating of Arabic letters that are different by Siam language for phonology problems, simplify the material of binyah kalimah and the material of mawaqi’ al i’rob for morphology problems, the giving of patterns of jumlah ismiyyah and jumlah fi’liyah and their examples for syntax efficiency problems. The alternative solutions to the non-linguistic problem are the use of learning methods that are varied and in accordance with the learning objectives, student conditions, and the material taught for the problems in the learning method, the use of learning media that are varied for the problems in the learning media, developing students' enthusiasm by learning Arabic for the problems in students.